2019
DOI: 10.1002/cm.21515
|View full text |Cite
|
Sign up to set email alerts
|

Nesprin‐2G knockout fibroblasts exhibit reduced migration, changes in focal adhesion composition, and reduced ability to generate traction forces

Abstract: The nuclear envelope protein nesprin‐2G is a component of the linker of nucleoskeleton and cytoskeleton (LINC) complex and is responsible for mechanical and signaling crosstalk between the nucleus and cytoskeleton. A prior study has demonstrated that nesprin‐2G knockout mice show delayed wound healing. The goal was to elucidate the mechanism underlying the delayed wound closure in this mouse model. Primary fibroblasts from wild‐type and knockout neonatal mice were isolated. Knockout cells exhibited decreased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…Because LINC complex disruption also reduced cell proliferation (Figure S2 nesprin-1 or nesprin-2 (King et al, 2014). Additional studies have shown delayed migration in LINC-disrupted fibroblasts (Luxton et al, 2010;Lombardi et al, 2011;Woychek and Jones, 2019). One notable observation in our movies of the wound healing assay was that the migratory behavior of DN-KASH expressing cells was more "chaotic" (Movie 4, Movie 5)…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Because LINC complex disruption also reduced cell proliferation (Figure S2 nesprin-1 or nesprin-2 (King et al, 2014). Additional studies have shown delayed migration in LINC-disrupted fibroblasts (Luxton et al, 2010;Lombardi et al, 2011;Woychek and Jones, 2019). One notable observation in our movies of the wound healing assay was that the migratory behavior of DN-KASH expressing cells was more "chaotic" (Movie 4, Movie 5)…”
Section: Discussionmentioning
confidence: 81%
“…Of note, a prior study showed that inhibition of phosphorylation of Y1065 of vinculin leads to a uncontrolled exchange of vinculin and reduced cell adhesive forces (Küpper et al, 2010), suggesting that the change in phosphorylation state of FA proteins observed in endothelial cells expressing DN-KASH is indicative of impaired FA dynamics and reduced adhesivity. In addition two recent studies have shown that loss of nesprin-1 (Nguyen et al, 2019) or nesprin-2G (Woychek and Jones, 2019) negatively affect cell migration, further suggesting a relationship between the LINC complex and cell-matrix adhesion (Nguyen et al, 2019), potentially through direct cytoskeleton force transmission between these two regions of the cell. Notably, one of these studies showed that loss of nesprin-1 affected ERK and FAK signaling (Nguyen et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Movement in Cells Expressing a Muscle Disease-Associated Variant of Lamin A Nesprin-2 and FHOD1 knockdown or nesprin-2 knockout in fibroblasts inhibits nuclear movement (Kutscheidt et al, 2014;Luxton et al, 2010;Woychek and Jones, 2019). To test the impact of the phosphorylation of nesprin-2 or FHOD1 on nuclear movement, phosphomimetic and unphosphorylatable forms of these proteins were expressed in fibroblasts depleted of the endogenous proteins (Figures S4A and S4B).…”
Section: Unphosphorylatable Fhod1 Rescues Nuclearmentioning
confidence: 99%
“…Cyclic stretch stimulation induces phenotypic switching of VSMCs through the transcriptional regulators Yes-associated protein (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ) signaling pathway (Wang et al, 2018). Although several studies have reported the biochemical or biomechanical factors involved in the stimulation of VSMC phenotypic transition, limited information is available about the effect on the mechanical environment of intracellular nucleus, including morphology and mechanical properties of the nucleus and intracellular forces exerted on the nucleus that are majorly involved in various cellular functions, such as cell migration (Woychek and Jones, 2019;Renkawitz et al, 2019) and proliferation (Versaevel, 2012; as well as the pathological conditions (Hoorntje et al, 2017).…”
Section: Introductionmentioning
confidence: 99%